PCR markerbased analysis of wild and cultivated yams (Dioscorea spp.)in Nigeria: genetic relationships and implication for ex situ conservation - Mignouna, H.; Abang, Mathew M.; Wanyera, N.; Chikaleke, V.; Asiedu, Robert; Thottappilly, G. (Springer, 2005)
Reliable characterization of the variation among wild and cultivated yams in Nigeria is essential for improved management and efficient utilization of yam genetic resources. RAPD and double stringency PCR (DS-PCR) analyses were used to investigate genetic relationships and the extent of redundancy among 30 accessions of two cultivated, and 35 accessions of four wild yam species collected from Nigeria. Twenty-five selected random decamer and two microsatellite primers were used individually and in combination to generate DNA profiles for each accession of the six Dioscorea species. The number of amplified fragments varied from 7 to 18 fragments per primer/primer combination. Different levels of intraspecific genetic diversity were found, with Dioscorea rotundata Poir. being the most variable. Based on identical profiles for the RAPD and DS-PCR primers, 12 duplication groups consisting of a total number of 37 accessions were observed in the present study. An UPGMA analysis grouped the majority of plants according to the species. Cultivated yams belonging to the D. cayenensis–rotundata species complex, which were classified into seven morphotypes/varietal groups, could be clearly separated into two major groups corresponding to D. rotundata Poir. and D. cayenensis Lam. D. cayenensis cultivars exhibited a low level of intraspecific variation and were genetically close to the wild species Dioscorea burkilliana J. Miège. D. rotundata cultivars classified into six varietal groups showed a high degree of DNA polymorphism and were separated into two major groups that appeared most closely related to Dioscorea praehensilis Benth. and Dioscorea liebrechtsiana de Wild. We propose, based on these results, that cultivars classified into D. cayenensis should be considered as a taxon separate from D. rotundata. The implications of intraspecific variability for the ex situ conservation of wild and cultivated yam germplasm in Nigeria are discussed.